2016
DOI: 10.1136/sextrans-2016-052699
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure prophylaxis (PrEP) for men who have sex with men in Europe: review of evidence for a much needed prevention tool

Abstract: In many Western countries with good coverage of antiretroviral treatment (ART) programmes the annual number of HIV infections is still high and not (yet) declining among men who have sex with men (MSM). This might indicate that antiretroviral treatment roll-out alone will not turn around the course of the epidemic and that new, additional tools are needed. Antiretrovirals used as prevention tools for people not yet infected with HIV, such as pre-exposure prophylaxis (PrEP) could be such important additional to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 56 publications
(51 reference statements)
1
30
0
Order By: Relevance
“…PrEP can be administered daily or on demand (before and after a sexual contact) [ 3 ], with both regimens demonstrating an effectiveness of 86% [ 5 , 6 ] that we used in our analysis. Our choice of modeling daily PrEP only was motivated by the interim findings on the preference of PrEP regimes in the AMPrEP project, which showed that 72% of participants chose to start daily PrEP [ 3 , 27 ]. We also obtained predictions of the model for other values of effectiveness and varying duration of using PrEP to reflect a real world setting where individuals are themselves responsible for obtaining and taking PrEP drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PrEP can be administered daily or on demand (before and after a sexual contact) [ 3 ], with both regimens demonstrating an effectiveness of 86% [ 5 , 6 ] that we used in our analysis. Our choice of modeling daily PrEP only was motivated by the interim findings on the preference of PrEP regimes in the AMPrEP project, which showed that 72% of participants chose to start daily PrEP [ 3 , 27 ]. We also obtained predictions of the model for other values of effectiveness and varying duration of using PrEP to reflect a real world setting where individuals are themselves responsible for obtaining and taking PrEP drugs.…”
Section: Discussionmentioning
confidence: 99%
“…At present preexposure prophylaxis (PrEP) is considered to be one of the most promising interventions to help end the HIV epidemic in this population [ 3 , 4 ]. Daily or intermittent PrEP uptake was shown to be effective in preventing HIV transmission among MSM in trials [ 5 , 6 ], cohort [ 7 ] and clinical practice studies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Event‐driven PrEP may address the challenges that appear to impede PrEP uptake and implementation, including concerns about PrEP's costs , side‐effects, physical burden, and adhering to PrEP on a daily basis . Event‐driven PrEP was shown to be cost‐effective and can pose a smaller financial burden on the health systems than daily PrEP . Furthermore, event‐driven PrEP may be more acceptable for MSM with less frequent risky sex or more concerns about PrEP's burden.…”
Section: Introductionmentioning
confidence: 99%
“…However, we could not have predicted the significant evolution that impacted the HIV prevention landscape soon after HMP was developed and implemented. While behavior change including CAI remains important, biomedical prevention interventions such as preexposure prophylaxis (PrEP) for HIV-negative individuals and treatment as prevention using antiretroviral therapy for positive individuals now has a more central role, among researchers and clinical practice (40)(41)(42). Unfortunately, questions about perceptions and usage of these strategies were not included in this study.…”
Section: Discussionmentioning
confidence: 99%